Determinants of the aortic pulse wave velocity index in hypertensive and diabetic patients: predictive and therapeutic implications. Issue 12 (December 2018) - Vallée, Alexandre; Yannoutsos, Alexandra; Temmar, Mohamed; Dreyfuss Tubiana, Céline; Spinu, Irina; Zhang, Yi; Protogerou, Athanase; Henry-Bonniot, Guillaume; Sosner, Philippe; Safar, Michel E.; Blacher, Jacques
Abstract : Objective: Aortic stiffness may provide information to classical risk factors information regarding cardiovascular risk. Aortic pulse wave velocity (PWV) can be measured by applanation tonometry but also theoretical PWV was calculated according to age, blood pressure, heart rate and sex. We aim to highlight biological and hemodynamic determinants of the aortic PWV index, that is the individually calculated [(measured PWV − theoretical PWV)/theoretical PWV] difference, in hypertensive diabetic patients. Methods: A cross-sectional study was conducted in 514 patients, involving normotensive and hypertensive patients and people with and without diabetes. Biological parameters were measured during day-hospital for cardiovascular screening. Hemodynamic parameters were determined by applanation tonometry. Multivariate regression analyses evaluated the PWV index determinants. Results: Hypertensive and/or diabetic population presents higher PWV index in correlation with the presence of proteinuria ( P = 0.0428) and previous cardiovascular events ( P = 0.0227). Hypertensive diabetic patients present a higher PWV index than the other patients ( P < 0.05). Presence of insulin therapy ( P = 0.0101) and the type 1 diabetes ( P = 0.0065) were positively and independently modulating PWV index in hypertensive diabetic patients. HDL cholesterol levels ( P = 0.0245) and absence of carotid ( P = 0.0468) plaques were independently modulating PWV index with a negative correlation in hypertensive without diabetes patients. C reactive protein levels were significantly associated with increased PWV index in hypertensive patients ( P = 0.0074) and in hypertensive and/or diabetic population ( P = 0.0184). Conclusion: PWV index was correlated with numerous cardiovascular risk factors, in addition of being a marker of age and hypertension. Therefore, this index appears as a cardiovascular risk integrator. Its use could be interesting in cardiovascular risk assessment and reduction strategies. Abstract : Supplemental Digital Content is available in the text